A ecopedagogia e sua relação com as práticas educativas ambientais formais existentes no sistema escolar toledano - Nepomoceno, Taiane Aparecida Ribeiro (2019)
The planet Earth passes through an environmental crisis, issued by circumstances of social, political and economic order. The dimensions affected by global crisis have placed on threatens the survival of civilization itself. So many looks have been released to the environment and to the forms of education geared to him. In this sense, environmental education has been discussed in several areas, including in schools. Note that your implementation depends on the transformation of practices, which are usually performed so punctual, meaningless to whom the practice. Within this context, emerges the Ecopedagogy you want to wake up to the look of the people to a way of being and being on the planet, emphasizing a harmonic coexistence between all members of the global community and these knowledge can be achieved by planetary citizenship. She amplifies the environmental education providing you with means to think about the environmental practices of other ways, signaling paths for your implementation. Has no intention to start again, on the contrary it proposes the ressignification of the existing environmental actions, as a permanent imperative of planetary reconstruction. In this way, this research sought to understand which are the curricular proposals presented by Ecopedagogy and in which it differs from the proposal of Environmental Education, regarding the environmental educational practices developed in the Basic Education schools, in the Municipality of Toledo-PR? The central objective was to analyze the practical activities for Environmental Education instituted in the Pedagogical Political Projects of four institutions of the Toledo school system, in order to elaborate indicators that corroborate with the creation and maintenance of the concept of planetary citizenship. This research is exploratory and uses bibliographic and documentary research techniques. The study of the documents was carried out based on the content analysis and, based on the analysis categories elaborated. Through the studies carried out, it was possible to verify that formal environmental practices are mostly carried out based on conservationist and pragmatic traits. It was also possible to identify some actions that are reductionist and punctual, being designed to change behavior, and this has made them fragile. It was noted that a large part of these environmental actions are not being carried out in a transversal and interdisciplinary way, as provided by the legislation. In general, the four institutions are slowly evolving in the process of overcoming traditional practices, and therefore, Ecopedagogy emerges in an incipient and timid way. But still, it is believed that Ecopedagogy represents a proposal that can change the way of living, learn, transform and improve the environmental actions developed by the analyzed institutions, a complex but not impossible challenge.